2013
DOI: 10.1017/s175173111200225x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of previous handling experiences on responses of dairy calves to routine husbandry procedures

Abstract: The nature of human-animal interactions is an important factor contributing to animal welfare and productivity. Reducing stress during routine husbandry procedures is likely to improve animal welfare. We examined how the type of early handling of calves affected responses to two common husbandry procedures, ear-tagging and disbudding. Forty Holstein-Friesian calves (n 5 20/treatment) were exposed to one of two handling treatments daily from 1 to 5 weeks of age: (1) positive (n 5 20), involving gentle handling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…In future studies, a positive sham-treated control group could be included to observe the effects of handling and external stressors on pain response scores. Stewart et al (2013) reported an increase in heart rate following ear tagging, but no significant changes in behaviour were noted. However, their study did not report on perioperative pain behaviour, whereas the present study did note discomfort during the procedure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In future studies, a positive sham-treated control group could be included to observe the effects of handling and external stressors on pain response scores. Stewart et al (2013) reported an increase in heart rate following ear tagging, but no significant changes in behaviour were noted. However, their study did not report on perioperative pain behaviour, whereas the present study did note discomfort during the procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, each animal received two tags (one in each ear) and one ear notch; however, the order of procedures was randomized for each animal. Ears were tagged using a standard flexible tag applicator (Allflex Australia Pty Ltd; Landmark Goulburn, NSW, Australia) as per normal farm practice with the tag attachment in the middle of each ear between the two main cartilage ridges (Stewart et al 2013). Ear notching was performed by removing a section from the edge of the ear in a pattern unique to the property.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…Increased HR after ear-tagging was found in calves (Stewart et al, 2013) similarly during the 5 min following hot-iron disbudding both with and without local anaesthesia (Stewart et al, 2008a). However, in the latter case, prolonged HR elevation was found only without local anaesthesia (up to 3 h) and sympathetic measure (LF/HF ratio) only increased following disbudding without local anaesthesia suggesting the efficiency of analgesia.…”
Section: Effect Of Pathological Disordersmentioning
confidence: 91%
“…Recently, several HR studies focused on the effect of an altered emotional state of the animals related to separation (Boissy and Le Neindre, 1997), weaning (Hopster et al, 1995), veterinary procedures (Waiblinger et al, 2004), early handling (Stewart et al, 2013), social interactions (Laister et al, 2011) and human contact (Rushen et al, 1999;Schmied et al, 2008a and.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a dearth of evidence regarding individual differences in cows with regard to cross-species sociality, though there is some evidence for acclimation to human handlers who provide positive handling experiences and interactions (Petherick, Doogan, Holroyd, Olsson, & Venus, 2009), which is unfortunately nonnormative (i.e., branding, disbudding, rough handling of infant and adult cows; see Schwartzkopf-Genswein, Stookey, & Welford, 1997;Stewart et al, 2013). Investigations to better understand individual differences in sociality and gregariousness in cows would be an important advancement in cow personality research.…”
Section: Personalitymentioning
confidence: 99%